Two-Scale Modelling of Reactive Powder Concrete. Part II: Numerical Simulations - DENISIEWICZ, Arkadiusz; KUCZMA, Mieczysław Sylwester (Engineering Transactions, 2015)
This article is the second part of a series about two-scale modelling of reactive powder concrete (RPC). In the first part [2] a method of modelling RPC microstructure was presented, the boundary value problem of mechanics for a representative cell at the micro scale was formulated and solved. In this part we will consider a method for determining material parameters at the macro level, and describe a technique of enforcement of boundary conditions upon an RVE as well as illustrate the theoretical considerations with results of numerical simulations. In the third part of the series we will present the validation of the proposed numerical model, based on the computational simulations of full size beams made of two RPC mixtures and own laboratory testing of the beams.